Peningkatan Pengetahuan tentang Bahaya HIV/AIDS melalui Permainan Ular Tangga di MTS Nahdlatul Ulama Ciamis - Yanti Srinayanti; Suhanda; Gita Nurmala; Ayunda Sekar; Rifan Agustian; Egi Putri Lestari; Silvi Mega Azahra; Fadrian Widya Augista; Adi Nurapandi (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction : HIV/AIDS is a contagious disease that can affect anyone. Prevention efforts promoted by the government are health education or socialization for the people of Indonesia. Objective: The purpose of this activity is to raise awareness about the dangers of HIV/AIDS through the game of snakes and ladders. Method: This study uses health education methods and the game of snakes and ladders in which each snake contains questions about HIV/AIDS. It was carried out with 4 students who were at MTS NU Ciamis with 28 students as respondents. Result: The result of this community service is that health counseling is carried out regarding increasing knowledge of the dangers of HIV/AIDS amoung 28 students of MTS NU Ciamis and there are differences in knowledge after counseling. Conclussion: Health education activities regarding the dangers of HIV/AIDS carried out to students at MTS NU Ciamis, can increase knowledge about the dangers of HIV/AIDS.